Mustafa Zihni: His Life, Administrative and Cultural Roles in Ottoman Empire - ڕەشید, سامان مستەفا (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
Mustafa Zihni is a son of Hussain Beg from Baban Clan (family), who was born in Sulaimanyiah in (1266 AH- 1850 A.D.), He studied fundamentals of sciences at school, and he was tutored Islamic Law (Jurisprudence) and languages such as: Turkish, Arabic, and Persian, so he could speak Kurdish, Arabic, Persian, and write in Turkish. He was a significant statesman in the Ottoman State, he took vital administrative posts as Wāli and a resident governor (mutasarif) through his entire life. The most important locations he held position of resident governor were: Karbala, Qozan, Gumushkhana, Barat, Burdur, Tarablus of Sham, Antalya, Bolu. Later, He was also appointed as Wāli in Adana, Yaniya and Hijaz. Needless to say, he was one of the distinguished features in the Ottoman State administration in the end of 19th century and the beginning of 20th century. In addition to his administrative roles and duties, he authored many books, and published in Ottoman Turkish; such as (Ilm w Islam, Islamda Khalafat, Qawai Maanawya, Tawsia Mazuniyat. It is worth mentioning that Mustafa Zihni had six children, his sons played vital role in the fields of education, journalism, culture, and administration in the Ottoman State. His most prominent son was Babanzadah Ahmmad Naaim, who taught philosophy and psychology in Istanbul University, he was the first one who translated (Sahih Bukhari) from Arabic into Ottoman Turkish, he also translated philosophical concepts from French. Ismail Haqii Babanzadah, another son of his, who was then one of the well-known journalist and author in his in Istanbul. He also held the post of minister of education. However; during the establishment of Turkey republic, he was offered many administrative posts, but he rejected them and preferred having solitude life for the rest of his life, He passed away in 1929 in Istanbul, and he was buried in (Adrna Qapi) graveyard.